Development of instant rice-based porridge with chicken (Chicken arroz Caldo) - Magsuci, Carol de la Peña
This study developed an acceptable instant rice porridge with chicken or arroz caldo product. It was part of UP PhilRice research project entitled "Rice and Rice-Based Disaster Foods". The first phase of the study dealt with the selection of the most acceptable arroz caldo formulation by sensory evaluation with 49 panelists found form 3 published recipes. The formulation of Perez (1953) was established as the most acceptable formulation. The conventionally-cooked formulation (Perez 1953) was described to have a color between white and cream rice base color, moderately soft rice texture, near neither thin nor thick consistency,, slightly distinct aroma, moderately soft chicken texture and moderately distinct flavor. Based on the results of the panelists' evaluation, improvement of the formulation involved 18% in water content and 200% increase in pepper to develop better consistency and flavor. The instant arroz caldo was developed by preparing instant rice, formulation of instant arroz caldo mix, use of TVP as chicken meat analog, and compounding of instant product. The instant rice was prepared by hydrating Malagkit Sungsong rice in 0.5% CaCl2 solution at 50°C for 30 min., gelatinization using steam under pressure at 15 psi and 121.5°C for 6 min, drying by convection air drying at 55°C for 55 min to attain 8-10% moisture content, and rice puffing using oil immersion method at 200°C for 2 sec. Rehydration of the instant product was done by boiling in water for 5 min using a 1;6 instant mix to water ratio. Rehydrated product was found to be not significantly different at 55 level of significance from its conventionally-cooked prepared equivalent in terms of sensory characteristics. The rehydrated instant arroz caldo sample was liked moderately in terms of rice-based porridge consistency, rice texture, chicken meat texture, overall flavor and overall acceptability and was liked between slightly like and moderately like in terms of rice base color, aroma, and chicken meat color. The rehydrated instant arroz caldo sample was described as cream to slightly yellow in rice base color, neither thin nor thick inconsistency of porridge, slightly distinct aroma, moderately to very soft rice texture, slightly soft chicken meat texture, light brown chicken meat color, and slightly distinct flavor. The pH values of the compounded and rehydrated instant product were 5.8 and 6.5, respectively, The Aw values were determined to br 0.410 for the compounded sample and for the rehydrated instant product, 0.923. The TPC and YMC of the compounded instant product were〖10〗^4 cfu/g for TPC and 〖10〗^2 cfu/g YMC. The cost per serving of 43.5 g (dry weight) developed product,(150 g rehydrated), was computed at PhP 11.73. Recommendations for future product development included improvement of flavor, consistency and color of the instant product; selection of the proper packaging materials of the instant product and storage stability studies; nutritional analyses of the developed product and upscaling the production of the product from laboratory to commercial-scale production.